2020
DOI: 10.1002/vzj2.20088
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus cycling and spring barley crop response to varying redox potential

Abstract: For arable soils, it is not clear whether closing a controlled drainage system leads to P mobilization due to water table rise and associated changes in redox-induced biogeochemical processes. Therefore, we investigated P mobilization at different redox conditions using three spring barley (Hordeum vulgare L.) cropped lysimeters filled with monoliths of arable northeastern German soil profiles. Pore water samples were collected weekly from three different depths, and dissolved (<0.45 μm) element concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…For example, under reducing conditions, that is, with low or no supply of oxygen as an electron acceptor, electrons can instead be transferred to, for example, Fe(III) (Megonigal et al., 2004; Reddy & DeLaune, 2008), resulting in Fe reduction into soluble Fe(II), along with release of nutrients previously adsorbed to the Fe(III) oxides. As a result, a release of organic P compounds was observed in temperate arable soils with a shift from oxic to reducing conditions due to increased soil moisture (Baumann et al., 2020). Thus, water level and associated redox conditions may influence the availability of nutritional elements for biological processes, the consequences of which will be discussed in more detail in the following chapters.…”
Section: Molecular‐scale Processes Incorporating Water Into Nutrient ...mentioning
confidence: 99%
“…For example, under reducing conditions, that is, with low or no supply of oxygen as an electron acceptor, electrons can instead be transferred to, for example, Fe(III) (Megonigal et al., 2004; Reddy & DeLaune, 2008), resulting in Fe reduction into soluble Fe(II), along with release of nutrients previously adsorbed to the Fe(III) oxides. As a result, a release of organic P compounds was observed in temperate arable soils with a shift from oxic to reducing conditions due to increased soil moisture (Baumann et al., 2020). Thus, water level and associated redox conditions may influence the availability of nutritional elements for biological processes, the consequences of which will be discussed in more detail in the following chapters.…”
Section: Molecular‐scale Processes Incorporating Water Into Nutrient ...mentioning
confidence: 99%
“…Dieter et al (2015) reported that sediment drying-re-flooding increased the proportion of labile and soluble forms of P. However, in this study lake sediments were dried at ambient temperature (20 C) up to 3% residual gravimetric moisture. Similarly, in a recent study Baumann et al (2020) investigated the effect of changes in soil redox potential due to water table fluctuation on P mobilisation in arable soils. Here, however, water level in the lysimeter was adjusted to mark wet (À25 cm water level depth) and dry (À80 cm water level depth) periods.…”
Section: Introductionmentioning
confidence: 99%